Spoken Language Interface for Mobile Devices - Freitas, J.; undefined; Dias, J.; Barros, M. (Proc. 3rd Language & Technology Conference: Human Language Technologies as a Challenge for Computer Science and Linguistics, Poznan, Poland, 2007)
In this paper, we present a set of optimizations for a spoken language interface for mobile devices that can improve the recognition accuracy and user interaction experience. A comparison between a speech and a graphical interface, when used to accomplish the same task, is provided. The implications of developing a spoken language interface and integrating speech recognition and text-to-speech modules for European Portuguese in a mobile device, are also discussed. The paper focuses in the speech recognition module and in an algorithm for name matching optimization that provides the user with a more comfortable interaction with the device. Usability evaluation trials have shown that spoken language interfaces can provide an easier and more efficient use of the device, especially within a community of users less experienced in handling mobile devices